If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3x-4)+10=5(x+4
We move all terms to the left:
2(3x-4)+10-(5(x+4)=0
We multiply parentheses
6x-(5(x+4)+10-8=0
| 3(y-5)=-39 | | j+78/3=-6 | | x2.8=1.6 | | -986=f+1 | | 2y-39=-5(y-2) | | 26x+6=78 | | 44=2w+w | | 2k+2-k=10 | | 7y=6y-0.5 | | 27y=-837 | | s/5+21=26 | | x+(x+1)=15 | | 0.5x^2-3x+18=14 | | 30=(c-91) | | 3x−6=-12 | | 9z-15=75 | | 180-x=1/3(x)+12 | | 5=k*7 | | 3x−6=-12=-12 | | v+23=99 | | 27=k*3 | | 6x^2-60x-1800=0 | | 50=k*7 | | X-14=9x+15 | | 1+2c=9 | | 7/6=x+4/8 | | 3/x=1/4 | | 4x+48=9x+8 | | 6+28x=131 | | 6/n=12/8 | | 7(g-82)=49 | | -a1=15 |